Tawny Crazy Ant - Stephanie K. Hill; Rebecca W. Baldwin; Roberto M. Pereira; Philip G. Koehler (EDIS)
As of 2012, tawny crazy ants have invaded 24 counties in Florida, parts of southeast Texas, and other areas of the southeastern U.S. The tawny crazy ant is considered a series pest. This species infests buildings and greenhouses, attacks crops, domestic animals, honeybee hives, displaces native ant species, and disrupts electrical equipment. This 3-page fact sheet covers the tawny crazy ant’s distribution, description, colonies, feeding habits, and pest status and control. Written by S. K. Hill, R. W. Baldwin, R. M. Pereira, and P. G. Koehler, and published by the UF Department of Entomology and Nematology, October 2013.